Persepsi Masyarakat dan Evaluasi Pembentukan Bumdes - Abidin, M. Faishol; Sugiyanto, Sugiyanto; Sujarwo, Sujarwo (Universitas Musamus, Merauke, Papua, 2024)
BUMDes activities fully utilize the potential of the village and are based on the needs of the village community. However, in practice, there are many BUMDes that have not developed well and eventually disbanded and are no longer operating. The purpose of the research is to see the community's knowledge about BUMDes (perception) and evaluate the background of BUMDes formation in Sumberejo Sub-district based on PERMEN RI No. 11 of 2021 and Bojonegoro Regency PERDA No. 4 of 2021 concerning Village-Owned Enterprises. This research is a quantitative descriptive research using questionnaires with respondents on perceptions are the general public in Sumberejo Sub-district and respondents on participation in the formation of BUMDes are village officials and community leaders who participated in the BUMDes formation deliberations. Public perception of BUMDes is almost more than 50% (>50%) of the community already knows about BUMDes, namely from the definition, purpose, name and type of BUMDes business in their respective villages, only 29.7% of the community are members of BUMDes membership. The results of the highest suitability of participation in the formation of BUMDes is from new ideas as much as 61.90% and the suitability of village community businesses is 59.05%. Evaluation of the background of formation as well as sustainable preservation on all criteria in accordance with the regulations with a value interval ≥ 50%. The formation of BUMDes is in accordance with the Regulation where the origin of BUMDes formed mostly from new ideas and utilizing existing community businesses.